Who selects the 'right' directors? An examination of the association between board selection, gender diversity and outcomes. (9th May 2014) - Hutchinson, Marion; Mack, Janet; Plastow, Kevin
Abstract: Using a sample of companies from the top 500 listed firms in Australia, we investigate whether the presence of a designated nomination committee and female representation on the nomination committee affect board gender diversity. We also examine whether gender diversity on the board affects firm risk and financial performance. We find that board gender diversity is significantly and positively associated with the presence of a designated nomination committee and that female representation on the nomination committee is a significant explanatory factor of increasing board gender diversity following the release of the 2010 Australian Securities Exchange Corporate Governance Council (ASXCGC) recommendations. Further, our results support the business case for board gender diversity as we find greater gender diversity moderates excessive firm risk which in turn improves firms' financial performance. Our results are robust after correcting for selection bias and controlling for other board, firm and industry characteristics.